Gandhi Meets Primetime: Globalization and Nationalism in Indian Television - Kumar, Shanti (University of Illinois Press, 2005)
Shanti Kumar's Gandhi Meets Primetime examines how cultural imaginations of national identity have been transformed by the rapid growth of satellite and cable television in postcolonial India. To evaluate the growing influence of foreign and domestic satellite and cable channels since 1991, the book considers a wide range of materials including contemporary television programming, historical archives, legal documents, policy statements, academic writings and journalistic accounts. Kumar argues that India's hybrid national identity is manifested in the discourses found in this variety of empirical sources. He deconstructs representations of Mahatma Gandhi as the Father of the Nation on the state-sponsored network Doordarshan and those found on Rupert Murdoch's STAR TV network. The book closely analyzes print advertisements to trace the changing status of the television set as a cultural commodity in postcolonial India and examines publicity brochures, promotional materials and programming schedules of Indian-language networks to outline the role of vernacular media in the discourse of electronic capitalism. The empirical evidence is illuminated by theoretical analyses that combine diverse approaches such as cultural studies, poststructuralism and postcolonial criticism.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; Inde (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

Planet TV: A Global Television Reader - Parks, Lisa; Kumar, Shanti (NYU Press, 2003)
From the 1967 live satellite program "Our World" to MTV music videos in Indonesia, from French television in Senegal to the global syndication of African American sitcoms, and from representations of terrorism on German television to the international Teletubbies phenomenon, TV lies at the nexus of globalization and transnational culture. Planet TV provides an overview of the rapidly changing landscape of global television, combining previously published essays by pioneers of the study of television with new work by cutting-edge television scholars who refine and extend intellectual debates in the field. Organized thematically, the volume explores such issues as cultural imperialism, nationalism, postcolonialism, transnationalism, ethnicity and cultural hybridity. These themes are illuminated by concrete examples and case studies derived from empirical work on global television industries, programs, and audiences in diverse social, historical, and cultural contexts. Developing a new critical framework for exploring the political, economic, sociological and technological dimensions of television cultures, and countering the assumption that global television is merely a result of the current dominance of the West in world affairs, Planet TV demonstrates that the global dimensions of television were imagined into existence very early on in its contentious history. Parks and Kumar have assembled the critical moments in television's past in order to understand its present and future. Contributors include Ien Ang, Arjun Appadurai, Jose B. Capino, Michael Curtin, Jo Ellen Fair, John Fiske, Faye Ginsburg, R. Harindranath, Timothy Havens, Edward S. Herman, Michele Hilmes, Olaf Hoerschelmann, Shanti Kumar, Moya Luckett, Robert McChesney, Divya C. McMillin, Nicholas Mirzoeff, David Morley, Hamid Naficy, Lisa Parks, James Schwoch, John Sinclair, R. Anderson Sutton, Serra Tinic, John Tomlinson, and Mimi White.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Identités diasporiques; _Nettoyé

Spaces of Television: Rethinking the Public/Private Divide in Postcolonial India - Kumar, Shanti (Channeling Cultures: Television Studies from India, 2014)
This chapter critically evaluates changing definitions of ‘public’ in Indian television in relation to discourses of globalization and media privatization. It examines the debate over the nationalist agenda of public broadcasting in India in relation to the demands for alternative models of broadcasting, and the rise of private commercial satellite channels since the 1990s. It also discusses how representations of traditionally private desires of sexuality and intimacy in soap operas, reality TV shows and music television are redefining the public in India. It outlines the ways in which private desire is made visible — and thus made public — through the convergence of the television screen, the cinematic screen, the computer screen, and the mobile screen. It argues that binaries of ‘public’ versus ‘private’ force us into either/or debates even though such category systems are always-already hybrid in postcolonial societies such as India.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Identités diasporiques; Inde (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)